Numerical and Experimental Investigations on the Inherent Stress State of Cold-bent Glass - Maximilian Laurs (Challenging Glass Conference, 2020)
In today’s architecture the bending of glass plays an important role in achieving free forms in modern façades. In addition to the usual procedure of hot bending glass sheets into the desired shape, the option of cold bending is being used more and more frequently. In this process a glass pane is bent into the desired shape and fastened to a substructure without prior heating and at low cost. This inherent bending state comes along with different beneficial but also with some unfavourable perks that have to be considered in the engineering process. The resulting influences on the strength of the glass and stiffness of the overall system are investigated in a German research project. In large-scale tests, special attention is paid to the established shape of the pane during the bending process and the resulting load on the steel substructure.